1 - ‘Down with the devil, Forward with Christ!’ A study of the interface between religious and political discourses in Zimbabwe - Ezra Chitando (African Sociological Review, 2002)
The relationship between religion and politics in Africa has been approached from a multiplicity of angles. Many commentators have ana lysed the role of churches in democratisation processes in the postcolonial period, while others have examined the impact of religion on ethnie imagination. African Traditional Religions and their contribution to African liberation struggles have also received considerable scholarly attention. This article builds upon the available reflections on religion and politics. lt examines the inte,face between religious and political dis courses in Zimbabwe from the late 1990s. While many scholars adopt a deterministic interpretative framework, I argue that there has been a dynamic interchange and free borrowing of phrases, catchwords and ideologies between the religious and political arenas. I also maintain that as the social, political and economic climate worsened in Zimbabwe, reli gious and political rhetoric became pronounced. Religion and politics injluenced each other in ways that call for a rethinking of traditional for mulations, I argue in the conclusion.